DETERMINED MODEL FOR COORDINATED REGULATION OF MOTOR TRANSPORT MOVEMENT ON HIGHWAY - V. P. Ivanov; V. N. Shut; O. J. Vaitsekhovich (Наука и техника, 2011)
The paper examines certain parameters of a determined model and its response to changes in these parameters. The determined model for bidirectional movement has been developed in the paper. The paper contains proposals for an optimization of the developed model which are intended for reduction of motor vehicle delays in front of an in-traffic light stop line along the main highway direction.